Sarcoid-like reaction at the patient with chronic hepatitis C on a background of antiviral therapy - A. V. Lapshin; N. I. Kokina; M. V. Mayevskaya; I. A. Sokolina; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To present a case of sarcoid-like reaction development, induced by antiviral therapy, in patient with chronic hepatitis C, as well as the management approach for this patient.Features of clinical case. At female 53 year-old patient with chronic hepatitis C (HCV RNA+, genotype 1b) of moderate activity (А2, F0 by METAVIR scale) development of granulomatous pulmonary lesion accompanied by fever, respiratory failure, asthenic syndrome had been observed on the 22-nd week of antiviral therapy by PEG-interferon and ribavirin. Sarcoid-like reaction has been diagnosed. At computer tomography of the chest organs bilateral miliary monomorphic dissimination on a background of interstitial changes was found, intrathoracic lymph nodes were increased in their number and size. Cessation of antiviral therapy did not result in improvement of patient’s state within 2 months. Immune-suppressive therapy by methylprednisolon and phosphogliv was prescribed, that resulted in complete regression of clinical symptoms and radiological changes in the lungs. Sustained virologic response was preserved in the patient.Conclusion. Sarcoid-like reaction falls to rare unpredictable complications of antiviral therapy. Expected side effects of antiviral therapy can mask development of sarcoid-like reaction.